Does physical activity change predict functional recovery in low back pain? Protocol for a prospective cohort study - Hendrick, P.; Milosavljevic, S.; Bell, M.; Hale, L.; Hurley, D.; McDonough, S.; Melloh, Markus; Baxter, D. (Biomed Central Ltd, 2009)
Background: Activity advice and prescription are commonly used in the management of low back pain (LBP). Although there is evidence for advising patients with LBP to remain active, facilitating both recovery and return to work, to date no research has assessed whether objective measurements of free living physical activity (PA) can predict outcome, recovery and course of LBP. Methods: An observational longitudinal study will investigate PA levels in a cohort of community-dwelling working age adults with acute and sub-acute LBP. Each participant's PA level, functional status, mood, fear avoidance behaviours, and levels of pain, psychological distress and occupational activity will be measured on three occasions during for 1 week periods at baseline, 3 months, and 1 year. Physical activity levels will be measured by self report, RT3 triaxial accelerometer, and activity recall questionnaires. The primary outcome measure of functional recovery will be the Roland Morris Disability Questionnaire (RMDQ). Free living PA levels and changes in functional status will be quantified in order to look at predictive relationships between levels and changes in free living PA and functional recovery in a LBP population. Discussion: This research will investigate levels and changes in activity levels of an acute LBP cohort and the predictive relationship to LBP recovery. The results will assess whether occupational, psychological and behavioural factors affect the relationship between free living PA and LBP recovery. Results from this research will help to determine the strength of evidence supporting international guidelines that recommend restoration of normal activity in managing LBP. Trial registration. [Clinical Trial Registration Number, ACTRN12609000282280]. © 2009 Hendrick et al; licensee BioMed Central Ltd.